Sama celebrations ritual, music, dance of Sama Dilaut and Sama Badjau in southern Philippines and north Borneo - Hussin, Hanafi; Santamaria, MCM; Institute of Ocean & Earth Sciences University of Malaya (Kuala Lumpur, Malaysia Institute of Ocean and Earth Sciences, University of Malaya Press, 2013)
Sama identity, as the chapters in this volume indicate, is University of Malaya closely linked with artistic expressions. It appears that among the most salient of these expressions in terms of creating and transmitting identity are music and dance. Along with other elements of ritual in which they are embedded, these traditional forms constitute veritable sources of collective memory, conceptions of their cosmos, and are by way of practice and belief considered to be indispensable media for encounters with the spirit world, most importantly their omboh or ancestors who are believed to be constantly looking over their welfare.
Introduction -- Sama indetities -- Celebrating with the Lord of the Sea (Tuan Laut) : The Pagkanduli of the Sama Dilaut of Sitangkai, Tawi-Tawi, Southern Philippines -- Celebrations with the Ancestors: Magduwata Ritual of Sama Bajau in Bumbun Island, Semporna, Sabah -- Song of Belonging: Vocal Music among the "Sea Nomads' of the Sulu and Celebes Seas -- Contemporary Trends and Influence in Music and Dance of Sama -- Sangbay-Igal (Tribute Song-Dance) Performance Across Real and Cyber Spaces -- Dance as Ritual, Dance as Celebration -- Tradition and Change amongs the Bajau of Semporna, Sabah -- Igal Kata-Kata (Narrative Igal): Examining Approaches to the Interpretation of Folk Tales in Sama Traditional Dance Choreography -- Pamansak (Pangalay or Igal): On Labels, Dominant Discourses and Diversity in Philippine Dance Research -- Conclusion: Change, Continuity and Creative Preservation of Sama Tradition
Includes bibliographical references.
Keywords: Badjau (Southeast Asian people) .; Bajau (Southeast Asian people) -- Ritess and ceremonies; Bajau (Southeast Asian people) -- Social life and customs .; Bajau (Southeast Asian people) -- Philippines -- Tawi-tawi.; Bajau (Southeast Asian people) -- Malaysia -- Sabah; Tawi-Tawi (Philippines) -- Social life and customs; Sabah (Malaysia) -- Social life and customs